Seulangkȇ as a Model for Enhancing Principal Competence in South Aceh: a Study on the Cultural Approach Effectiveness - Maidar, Maidar; Gultom, Syawal; Darwin, Darwin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The impact of culture on learning has been extensively acknowledged by authorities such as Vygotsky. This study aimed to evaluate the efficacy of the Acehnese culture-based training model, Seulangke, and to enhance the competencies of state secondary school administrators in South Aceh Regency, Indonesia. This research employs a qualitative methodology with a cultural perspective. This paper employs a pre-experimental design characterized by a one-shot case study involving 27 principals in South Aceh. Data collection was conducted by testing and paperwork, thereafter analyzed with the t-test method utilizing SPSS version 23. Differences in learning results exist between training participants utilizing the Jigsaw training model (experiment A) and the Seulangkê model (experiment B) among school principals. The study stated that the experimental data indicated a disparity in learning outcomes between experiment A, which yielded a score of 69.63, and experiment B, which achieved a score of 75.00. This indicates that the application of Experiment B (Seulangkê Model) in education is superior to the control Experiment B (Jigsaw Model). The statistical examination of the